2016
DOI: 10.1007/s40279-016-0565-2
|View full text |Cite
|
Sign up to set email alerts
|

Leisure-Time Physical Activity in Pregnancy and Maternal-Child Health: A Systematic Review and Meta-Analysis of Randomized Controlled Trials and Cohort Studies

Abstract: Our findings support the promotion of LTPA in pregnancy as a strategy to improve maternal and child health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
146
2
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(161 citation statements)
references
References 107 publications
9
146
2
4
Order By: Relevance
“…In terms of life style during pregnancy, physical activity (PA) practice has shown beneficial maternal and child health effects . Current evidence suggests a lower incidence of pregnancy‐related complications such as gestational diabetes, preeclampsia, preterm birth and postpartum depression . In addition, studies focusing on the neonatal period and child growth have shown a lower incidence of low birthweight, improved child body composition (lower body fat percentage), and a greater ponderal index …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of life style during pregnancy, physical activity (PA) practice has shown beneficial maternal and child health effects . Current evidence suggests a lower incidence of pregnancy‐related complications such as gestational diabetes, preeclampsia, preterm birth and postpartum depression . In addition, studies focusing on the neonatal period and child growth have shown a lower incidence of low birthweight, improved child body composition (lower body fat percentage), and a greater ponderal index …”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Current evidence suggests a lower incidence of pregnancy-related complications such as gestational diabetes, preeclampsia, preterm birth and postpartum depression. 14,15 In addition, studies focusing on the neonatal period and child growth have shown a lower incidence of low birthweight, improved child body composition (lower body fat percentage), and a greater ponderal index. 16 Specifically, for neurodevelopment, research in animal models have shown that PA during pregnancy is associated with improved neurogenesis, proliferation in learning and memory cells and brain plasticity among other neurobiological processes.…”
mentioning
confidence: 99%
“…A large body of research has shown that physical activity during pregnancy provides many maternal health benefits, such as management of GWG, and reduction in the risk of GDM as well as pre-eclampsia [17,18]. The exact effect of maternal physical activity on foetal growth and development remains controversial [1,19,20], yet it is essential that pregnant women are physically active enough to maintain a healthy bodyweight and prevent increased GWG, particularly when pre-pregnancy body mass index (BMI) are high [10].…”
Section: Maternal Nutrition and Physical Activity During Pregnancymentioning
confidence: 99%
“…The exact effect of maternal physical activity on foetal growth and development remains controversial [1,19,20], yet it is essential that pregnant women are physically active enough to maintain a healthy bodyweight and prevent increased GWG, particularly when pre-pregnancy body mass index (BMI) are high [10]. Much of the available intervention literature is from high-income countries (HICs), with only a small proportion originating from LMICs [17], and none coming from Africa. A recently conducted systematic review found only five studies that had measured physical activity during pregnancy in Africa; moreover, none of these were intervention studies [21].…”
Section: Maternal Nutrition and Physical Activity During Pregnancymentioning
confidence: 99%
“…Participating in 20–30 minutes of moderate intensity PA on most days of the week (approximately 150 minutes per week) [1], as recommended by the American College of Obstetricians and Gynecologists (ACOG) [2], provides various benefits such as reduced risk of excessive gestational weight gain, gestational diabetes mellitus [3,4] and preeclampsia [5]. In addition, women who are physically active during pregnancy benefit from increased cardiovascular fitness and muscular strength [6], as well as psychological benefits and improved mental health [7].…”
Section: Introductionmentioning
confidence: 99%